Precision a history of American warfare - Rogers, James (Manchester University Press, 2023)
"We think of precision warfare as a modern invention, closely associated with the Gulf War, the Kosovo Campaign and drone technologies. But its origins go back much further in history. As historian James Patton Rogers reveals, this quest to achieve precision in war began in 1917, during the early years of powered flight in the United States. This means that precision has been a significant, if not always achievable, feature of American strategic thought for more than a hundred years. Patton Rogers takes readers on a journey through the twentieth century, highlighting the innovative thinkers of the First World War, the experimental technologies of the Second World War and the surprising Cold War nuclear strategies that made precision the dominant feature it is today. From Russia's offensive war in Ukraine to Libya, Ethiopia and Nagorno-Karabakh, the conflicts of the twenty-first-century are being fought with precision weapons. Patton Rogers answers two enduring questions: why has precision been such a defining feature of US military thinking? And how has this ambition shaped public and military perceptions of war today?"
Literaturangaben, Register
Keywords: Geschichte 1917-1991; Präzisionsgelenkte Munition; Krieg; Zielgenauigkeit; USA; Military art and science / United States / History; Tactics / History; Art et science militaires - États-Unis - Histoire; Tactique militaire - Histoire